2019
DOI: 10.1021/acsomega.9b00676
|View full text |Cite
|
Sign up to set email alerts
|

Control of Functionalities in GO: Effect of Bronsted Acids as Supported by Ab Initio Simulations and Experiments

Abstract: Graphene oxide (GO) is an attractive precursor for graphene, provided by the well-known wet-chemical oxidative process. The intercalation of acid in graphite is considered as a crucial step, and its subsequent oxidation holds special relevance in synthesis. So far, the above chemistry is dominated by usage of H 2 SO 4 . Recently, H 3 PO 4 appeared as a suitable intercalant for graphite. However, its role is not well und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 77 publications
1
6
0
4
Order By: Relevance
“…This can be further visualized from the TEM images shown in Figure 4c,d. The selected area electron diffraction (SAED) pattern of the modified GO-PEG showed distorted fringes, shown in Figure 4c′, corroborating well with the literature, 59 whereas deposited Fe ATA on GO-PEG revealed well-defined lattice fringes (as can be seen in Figure S2g) suggestive of retention of crystallinity confirming the crystalline nature of iron oxide NPs, shown in Figure 4d′, which is in good agreement with the XRD analysis. Figure S7 clearly shows that the GO-PEG surface assisted in decreasing the average particle size of loaded Fe ATA substantially.…”
Section: Resultssupporting
confidence: 88%
“…This can be further visualized from the TEM images shown in Figure 4c,d. The selected area electron diffraction (SAED) pattern of the modified GO-PEG showed distorted fringes, shown in Figure 4c′, corroborating well with the literature, 59 whereas deposited Fe ATA on GO-PEG revealed well-defined lattice fringes (as can be seen in Figure S2g) suggestive of retention of crystallinity confirming the crystalline nature of iron oxide NPs, shown in Figure 4d′, which is in good agreement with the XRD analysis. Figure S7 clearly shows that the GO-PEG surface assisted in decreasing the average particle size of loaded Fe ATA substantially.…”
Section: Resultssupporting
confidence: 88%
“…1); this pattern, shows a peak around 2 θ = 10° which normally is observed when the Hummers' method is used for the synthesis of graphene oxide. 27,29 In Fig. 1 the diffraction pattern from ZnNP coincides with JCPSD card 01-007-2551.…”
Section: Resultsmentioning
confidence: 54%
“…In addition, co-acid molecules form hydrogen bonds between them, which increases the intercalation distance between graphite layers. As a result, it was reported that the interlayer spacing of graphite (3.35 Å) increases significantly over~8 Å [19], thereby decreasing the interlayer interactions between graphenes, as schematically shown in Figure 1a. After preparation of GOs with (and without) the intercalation step using co-acids, and their subsequent exfoliation in waters, the lateral size of L-GO flakes was 150 ± 29 µm (measured by 51 flakes), whereas that of GO flakes was 28 ± 24 µm (measured by 65 flakes; Figure 1b), although both exfoliations were performed using the same procedure (see experimental section).…”
Section: Resultsmentioning
confidence: 97%
“…− with graphenes in HOPG. This acid-based intercalation−oxidation chemistry of graphite is well known: H 3 PO 4 can be intercalated effectively between graphenes, and H 2 SO 4 predominantly causes the oxidation of graphenes [19,20]. In addition, co-acid molecules form hydrogen bonds between them, which increases the intercalation distance between graphite layers.…”
Section: Resultsmentioning
confidence: 99%